Seasonal Variations of Temperature, Salinity and Turbidity of the Lembeh Strait’s waters, North Sulawesi - Simon I. Patty; Rikardo Huwae; Ferdimon Kainama (Sam Ratulangi University, 2020)
Research on seasonal variations of temperature, salinity and turbidity of the Lembeh Strait’s waters were carried out in March 2016 to February 2017. Observations of temperature, salinity and turbidity were conducted using the Sonde EXO-2 multi parameter tool. The purpose of this study was to determine the seasonal effect on temperature, salinity and turbidity Lembeh Strait’s water. The results of the statistical analysis using ANOVA and Tuckey's test showed that the season affected the salinity and temperature, whereas no significant effect were observed on turbidity. Variations in temperature, salinity and turbidity are affected by external factors such as weather, wind and seasonal current patterns occurred in these waters. The conditions of temperature, salinity and turbidity of sea water in Lembeh Strait are still adequate for marine life.Keywords: temperature, salinity, turbidity, oceanography, Lembeh Strait